2014
DOI: 10.1080/00032719.2014.888722
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tryptophan using ap-Sulfonated Calix [4,6,8]arene Modified Gold Electrode

Abstract: The ability of p-sulfonated calix[n]arenes (n ¼ 4, 6, 8) to form complexes with tryptophan was studied. The electrochemical properties of these complexes immobilized on gold surfaces were examined by cyclic voltammetry. Parameters affecting the performance of the modified electrodes including the arene concentration, scan rate, applied potential, and pH were optimized. Under the optimal conditions, the method had a linear response to tryptophan between 1 Â 10 À7 M and 1 Â 10 À5 M with a detection limit of 3 Â… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…This may be attributed to the interaction between the -NH 2 + of tryptophan and the -SO 3 -of calixarene, and the cavity size of SC4A may be more appropriate for tryptophan than SC6A and SC8A. This finding was consistent with the trend observed in molecular modeling calculation results, 45 as shown in Fig. 10.…”
Section: Trptophan−scna Interactionssupporting
confidence: 94%
See 1 more Smart Citation
“…This may be attributed to the interaction between the -NH 2 + of tryptophan and the -SO 3 -of calixarene, and the cavity size of SC4A may be more appropriate for tryptophan than SC6A and SC8A. This finding was consistent with the trend observed in molecular modeling calculation results, 45 as shown in Fig. 10.…”
Section: Trptophan−scna Interactionssupporting
confidence: 94%
“…To make a distinct comparison with previous literature reported methods, the characteristics of different electrochemical sensors for tryptophan are shown in Table 1. [37][38][39][40][41][42][43][44][45][46] This indicated that the SC4A and cysteamine modified gold electrode was an appropriate platform for the electrochemical determination of tryptophan and had higher sensitivity to tryptophan (Table 1). Figure 9 shows that SC4A had the highest interaction with tryptophan in three SCnA (n = 4, 6, 8).…”
Section: Tryptophan−sc4a Interactionmentioning
confidence: 94%